2021
DOI: 10.1002/vnl.21889
|View full text |Cite
|
Sign up to set email alerts
|

The effect of iron oxide content on the structural and optical parameters of polyvinyl alcohol/graphene nanocomposite films

Abstract: The effect of iron oxide nanoparticles (Fe2O3 NPs) content on the structural and optical parameters of polyvinyl alcohol/graphene (PVA/G) blend has been investigated. Fe2O3 NPs were synthesized by the hydrothermal procedure. Nanocomposite (NC) films of PVA/G filled with different amounts of Fe2O3 NPs were equipped using the solution casting technique. The surface morphology, structural, and optical properties were examined by scanning electron microscope (SEM), X‐ray diffraction (XRD), and ultraviolet‐visible‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 81 publications
5
13
0
Order By: Relevance
“…This is caused by defects being produced, new states being created in the forbidden region, and the distance between the valence and conduction bands being lessened. 44 Similar behavior of decreasing the bandgap was observed for PVA/graphene/Fe 2 O 3 45 and PVA/PVP/SnS 46 systems.…”
Section: Uv-visible Analysissupporting
confidence: 65%
“…This is caused by defects being produced, new states being created in the forbidden region, and the distance between the valence and conduction bands being lessened. 44 Similar behavior of decreasing the bandgap was observed for PVA/graphene/Fe 2 O 3 45 and PVA/PVP/SnS 46 systems.…”
Section: Uv-visible Analysissupporting
confidence: 65%
“…The refractive index (n), optical conductivity (σ opt. ), dielectric parameters (real ε r, and imaginary ε i ) and surface/volume energy loss functions (SELF/VELF) were calculated as 4,13,40,41 :…”
Section: Methodsmentioning
confidence: 99%
“…Similar E g performance was reported in the literature. 5,13,53 It is reported that 5% of Gd 2 O 3 loading in PEG/PVA led to E g decrease from 4.70 to 3.98 eV. 55 The reduction in E g of PVP/PVA blend due to ACS doping refers to energy levels and defects created in its bandgap.…”
Section: Uv-visible Studiesmentioning
confidence: 99%
See 2 more Smart Citations